Ergonomic learning of the language of the urban environment - Yerbulatova, I. K.; Кurmanova B.Kh.; Magauova, A.T.; Almurzina, S.S. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The proposed article contains the materials of the currently ongoing ergonomic research focused on the development of the problem of ergodesign design related to the study of the phenomenon of human visual comfort when perceiving fragments of the urban environment. The terminological meaning of the word "ergonym" was found from the very beginning of the 20th century when there was no fixed concept yet. For this reason, the semantic meaning was inaccurate due to the greater flow of linguists and their opinion. But through the practical part, the authors managed to exclude similar onyms, thereby expanding the onomastic field. The practical part of the article consisted in the study of local ergonyms of the urban center of Western Kazakhstan, denoting objects serving motor vehicles. To collect onomastic research material, the following methods and techniques were used: sociolinguistic and psycholinguistic methods, level analysis when studying the linguistic characteristics of onyms; as well as general scientific methods, primarily modeling and experiment. The results of the study confirm the hypothesis that the language situation has a huge impact on the processes of formation of ergonymic space and, as a sociolinguistic phenomenon, reflects the level of the ethnic and cultural component of society